Libertad epistémica, libertad especulativa: acercamiento a uma lógica de la libertad o libertad lógica - Duplancic, Víctor (Revista Eletrônica Estudos Hegelianos, 2022)
The paper examines the possibility of finding in Hegel’s Science of Logic elements that support the possibility of a meta-category of Hegelian freedom. It discusses the positions that the Hegelian idea of freedom would be founded primarily on the category of ideality (Röttges), that the idea of freedom would be coextensive with the system but would be seen, within the Logic, clearly in the doctrine of the concept (Anghern) and that one could find an epistemic idea of freedom strongly linked to the cognitive aspects of Hegelian philosophy and independent of a freedom (Knappik) connected with the will. All this is framed in a proper theory of freedom in Hegel's philosophy that divides the dimensions of this idea into subjective freedom, intersubjective freedom and speculative freedom. The latter could be interpreted as a speculative metamodel of freedom in Hegel's philosophy.
Keywords: Science of Logic; Ideality; Georg Wilhelm Friedrich Hegel; Classical German Philosophy